Nata de coco production and processing - Hilario, Dino Cadiz (College of Engineering, 1994)
Capacity: 507,000 kg/year -- Total production cost: 8,396,313.00 -- Gross profit (before tax): 4,917,372.00 -- Annual rate of return on investment: 58.4% -- Payout time: 1.60 years